The impact of US regional business cycles on remittances to Latin America - Kristin Magnusson (Stockholm School of Economics, The Economic Research Institute (EFI), 2009)
The current economic slowdown in the United States and the decline in remittance growth to some Latin American countries have intensified the interest in the relationship between these variables. We investigate whether host country conditions affect remittance outflows to Latin America, focusing on the roles of regional U.S. business cycles, geographical variation in immigrant density and sectoral factors. Using quarterly data for 1995-2008, we find that remittance flows are strongly influenced by economic conditions in the specific regions of the U.S. where migrants are clustered, as well as in the sectors especially important for immigrants' employment opportunities. The results are in sharp contrast to previous research suggesting that remittance flows are relatively insensitive to fluctuations in the aggregate U.S. business cycle. Precise estimation of these linkages is also shown to matter for gauging the sensitivity of remittances to economic conditions in the home country, and hence the extent to which remittances might buffer domestic shocks as well as transmitting external ones.
Keywords: E32; F15; F22; F24; R11; 330; Remittances; Business Cycles; Central America; Mexico; United States; Regionaler Konjunkturzyklus; Rücküberweisung (Migranten); Lateinamerika; Mexiko; USA